PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Dewi, Linda Kania (Katalogis, 2015)
The Influence of Profitability, Leverage and Liquidity on Food and Baverages Industries’ Stock Price in Indonesia Stock Exchange This research is conducted to examine the influence of profitability, leverage and liquidity on Food and Baverages Industries’ Stock Price in Indonesia Stock Exchange in 2009 to 2012. The population consists of 12 food and beverages industries in Indonesia Stock Exchange in 2009-2012. By using purposive sampling method, the study selects 9 companies. The data is analyzed by murtiple linear regression and f-test is used to fetermine the reliability of the study with level of significance 5 %. The results slow that profitability, leverage and liquidity simultaneously affect the stock price. Partially, profitability affects the stock price positively and significantly, while leverage and liquidity have insignificantly on the stock price.